A laboratory-level control experiment for introducing predictive control to undergraduates. Issue 1 (1st January 2014) - Hedjar, Ramdane
Abstract This paper deals with a simple robust nonlinear control of a liquid-level system. The controller is based on one-step-ahead continuous time minimization of the predicted tracking error. We show different steps for complete engineering design from modeling and identifi cation to real-time implementation of the control algorithm. Simulations are performed to check the tracking performance of the controller. To validate the simulation results, the control algorithm is implemented in real-time to control the liquid-level system. This laboratory experiment is being implemented at King Saud University. During their classes, students learn how to use the nonlinear model of the liquid-level system to design a simple and robust controller that achieves the desired tracking performance both in simulation and in real-time implementation.